D PENGARUH MODERNISASI ADMINISTRASI PAJAK DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR PADA UPT. SAMSAT LUBUK PAKAM - Br. Sembiring, Dwi Savetri; Hasibuan, Thezar Fiqih Hidayat (Yayasan Cita Cendekiawan Al Khwarizmi, 2023)
This study aims to determine the effect of modernization of tax administration and tax sanctions on motor vehicle taxpayer compliance at the UPT. Samsat Lubuk Pakam. The type of research used in this research is quantitative. The population in this study is 97,800 motor vehicle taxpayers at UPT. Samsat Lubuk Pakam and the sample in this study were 100 motor vehicle taxpayer respondents at the UPT. Samsat Lubuk Pakam. The technique used by researchers for data collection is a survey method using questionnaire media (questionnaire). Data analysis used in this study was validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis test, t test, f test, and R2 test. The results showed that the effect of modernization of tax administration had a positive and significant effect on motor vehicle taxpayer compliance. Tax sanctions have a positive and significant effect on motor vehicle taxpayer compliance Based on the test rules it can be concluded that simultaneously the effect of modernization and tax sanctions has a positive and significant effect on motor vehicle taxpayer compliance.